Bacteriological Survey of the Frozen Prepared Foods Industry: III. Potato Products - Surkiewicz, Bernard F. (1967)
During sanitation-inspections of 29 potato-processing firms, 2,544 finished product units and 1,654 samples were collected and analyzed bacteriologically. The results of the bacteriological examination of finished French fries, fried potato cylinders, and dehydrated potatoes usually did not reveal the conditions of cleanliness under which they were produced. This was most likely due to the lethal effect of the terminal fry to which the French fries and potato cylinders are subjected, and because of the lethal effect of the dehydration temperatures used in processing the dehydrated potato products. However, as in most food-processing firms, line samples collected at each processing step reflect sanitary conditions and provide bacteriological support of inspectional evidence of plant insanitation. Most of the frozen stuffed baked potatoes examined were produced under poor sanitary conditions. But because this product is usually processed while hot, bacteriological examination of the finished product did not usually reveal the conditions of cleanliness under which they were produced. Again, inspectional observations were necessary for a full evaluation of the conditions of production. In contrast, frozen potato patties and frozen hash brown potatoes were more likely to reveal the conditions of sanitation under which they were produced as evidenced by the varying bacterial counts.